Socio-Economic Dependence of Peasant to Local Collector on Rice Farming System - Waza Karia Akbar (LPPM Universitas PGRI Sumatera Barat, 2018)
The poverty of peasant in Gunung Talang is caused by low income, low education and limited land. The purpose of this research is to analyze the bases of the peasant socio-economic dependence to the local collector (local assemblers) on rice farming system. The research is also analyzing the soci- economic relations of peasants and local collector on rice farming system. This research was conducted through the qualitative method with descriptive research type. The results show the socio-economic dependence due to peasant’s conditions. They do not have the capital to cultivate the agricultural land. Peasants are trapped in the patron clients system. They cannot get out from poverty. The socio-economic relation between the peasants and the local collector of rice farming occur because of a very strong relationship with their blood relatives (Dunsanak).